Effectiveness of a Prevention Program for Gender-Based Intimate Partner Violence at a Colombian Primary School - Garzón Segura, Anni Marcela; Carcedo González, Rodrigo J. (Frontiers in Psychology, 2020)
Intimate partner violence, particularly against women, is widely studied owing to its high rates, based on transnational data. Colombia, where this form of violence is considerably common, is no exception, and such violence increasingly occurs in ever younger couples (10−14 years old). Further, risk factors such as wide acceptance, the justification of intimate partner violence, extremely rigid traditional gender roles, and poor socio-emotional skills play a crucial role. In accordance with this reality, a gender-based intimate partner violence prevention program was designed, implemented, and evaluated for primary school children in Colombia, based on a review of successful preventive programs and an identification of the main predictors of intimate partner violence. The program was evaluated by using a quantitative study with a quasi-experimental design that included an experimental group and a control group. In total, 344 participants were involved in this study: 195 boys (56.7%) and 149 girls (43.4%) from the second and third grades of a primary school (average age: 7.8 years old) at a Colombian educational institution. There were 200 participants in the experimental group and 144 participants in the control group. The program’s effectiveness was evaluated by measuring three variable groups (gender stereotypes, the acceptance of violence, and socio-emotional skills) using reliable scales. To analyze the program’s effectiveness, mixed ANOVAs with a within-subjects factor (when the group was measured), two between-subjects factors (group and gender), and a covariate (age) were used. The results showed that the participants in the experimental group had lower scores in gender stereotypes, acceptance of peer aggression, and acceptance of physical violence against women compared to the control group. Conversely, they had higher scores in affective empathy after the intervention; both groups showed no significant differences before the intervention. This program is highly relevant because it proved to have a positive impact on the participants and is novel because of the lack of preventive programs that have been implemented in primary education and evaluated within the Colombian context.